NINA’S DISSOCIATIVE IDENTITY DISORDER IN ARONOFSKY’S MOVIE BLACK SWAN: A SEMIOTIC ANALYSIS - SUGESTI, LINDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Black Swan, Dissociative Ident it y Disorder, semiot ics, signs Movie is one of modern literary works that aim to deliver certain idea through audio-visual media. Movie consists of three elements: audio, visual, and verbal that are considered as signs. One movie that consists of implicit signs is Black Swan. Black Swan is a thriller psychological movie which tells about ballerina named Nina who has double ident it y called as dissociative identity disorder when she has to embody two characters in a project of a ballet show. This research, therefore aims to interpret the meaning of signs that represent Nina’s dissociative identity disorder in Black Swan. This research employs semiot ic theory by Peirce. Semiot ics is the study of signs. Everyt hing can be signs while it is interpreted as a sign. According to Peirce, sign is divided into three: icon, index and symbol. Dissociative identity disorder concept is also applies to find in the scenes that indicate Nina’s dissociative identity disorder.The result of this research found that there are three modes of signs in Black Swan. Those three modes of signs show that Black Swan tells about Nina’s dissociative identity disorder. Nina’s dissociative ident it y disorder signs portray three symptoms of dissociative identity disorder which come from Nina’s appearance changes, Nina’s behavior changes, and hallucinations.The writer suggests that the next researchers who want to use the same object that is movie, to apply other approaches such as psychological approach to interpret signs. By applying that approach it is expected that the research will be more comprehensive.